Calculating Areas of the Land Cover Types Using Multi-Temporal Images to Visualize Environmental Dynamics - Polina Lemenkova (country:UKR, 2015)
Целью исследования является картографирование заболоченных областей п-ова Ямал на основе применения разновременных спутниковых снимков Landsat TM и программного обеспечения (ПО) ILWIS GIS. В результате исследования была визуализирована экологическая динамика изменения избранных ландшафтов на Крайнем Севере России методами ГИС. he study aim is mapping swamp areas in the Yamal Peninsula using multi-temporal Landsat TM satellite images and software ILWIS GIS. The study technically based on the GIS techniques proved ecological dynamics by detected changes of the selected landscapes in the Far North of Russia.